PRO-UX: System Redesign Process for Improving the UX - Paiva, Joseane O. V.; Borges, Bosco; Duarte, Paulo; Santos, Ismayle S.; Andrade, Rossana M. C.; Lelli, Valéria (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
System redesign is a software modernization strategy that consists of restructuring a solution to provide a new graphical interface, improving the user experience, and using modern technologies while preserving relevant system functionalities. When it comes to enterprise applications, the challenge for redesign becomes greater. It is necessary to ensure that the system can operate according to existing business rules and that its operation will not compromise the integrity of the enterprise. This paper presents a process for redesigning systems to improve the user experience. We also describe a case study where we applied this process to redesign an enterprise application and share some lessons learned during the application redesign.